Frequency of Preterm Birth in Multiple Gestations Presenting at Mardan Medical Complex - Shehzadi, Shafaq; Amin, Nuzhat (Biological and Clinical Sciences Research Journal, 2025)
Multiple gestations are associated with increased maternal and neonatal risks, with preterm birth being one of the most significant contributors to perinatal morbidity and mortality. Identifying the frequency and associated factors of preterm birth in multiple pregnancies is essential for improving obstetric outcomes, particularly in resource-limited settings. Objective: To determine the frequency of preterm birth in women with various gestations presenting at Mardan Medical Complex, Mardan. Methods: This cross-sectional study was conducted in the Department of Obstetrics and Gynaecology, Mardan Medical Complex, Mardan, from August 15, 2024, to February 15, 2025. A total of 78 women with multiple gestations, defined as the simultaneous development of more than one fetus in the uterus, were included. Preterm birth was defined as delivery before 37 completed weeks of gestation. Data were analyzed using SPSS version 27, and preterm birth was reported as frequencies and percentages. Associations between variables were assessed, with a p-value <0.05 considered statistically significant. Results: The mean maternal age was 28.67 ± 6.94 years. Preterm birth occurred in 32 women (41.0%). Caesarean section was the predominant mode of delivery, accounting for 56 cases (71.8%). A statistically significant association was observed between maternal education and preterm birth, with 27 (84.4%) of women who delivered preterm being uneducated (p < 0.001). Conclusion: The frequency of preterm birth in multiple gestations was high in the present study. Lack of maternal education was significantly associated with an increased risk of preterm delivery. Targeted antenatal care and educational interventions may help reduce preterm birth rates in women with multiple pregnancies.